2022
DOI: 10.1186/s13072-022-00443-w
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer predictions of transcription factors mediating aberrant DNA methylation

Abstract: Background Aberrant DNA methylation is a hallmark of cancer cells. However, the mechanisms underlying changes in DNA methylation remain elusive. Transcription factors initially thought to be repressed from binding by DNA methylation, have recently emerged as being able to shape DNA methylation patterns. Results Here, we integrated the massive amount of data available from The Cancer Genome Atlas to predict transcription factors driving aberrant DNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…6 B, bottom panel), with low DNA methylation at their regulatory regions in GIV gliomas (Chi-square test for two independent groups, FDR < 0.05). A similar relation was found in other cancers [ 31 ]. Methylation of a specific cytosine within a c-Jun motif instance (1 cytosine in the c-Jun motif, “dvTGAGTCAYh”, HOCOMOCO version 11) within the promoters of putative c-Jun targets was found.…”
Section: Resultssupporting
confidence: 88%
“…6 B, bottom panel), with low DNA methylation at their regulatory regions in GIV gliomas (Chi-square test for two independent groups, FDR < 0.05). A similar relation was found in other cancers [ 31 ]. Methylation of a specific cytosine within a c-Jun motif instance (1 cytosine in the c-Jun motif, “dvTGAGTCAYh”, HOCOMOCO version 11) within the promoters of putative c-Jun targets was found.…”
Section: Resultssupporting
confidence: 88%
“…The methylation pattern of the promoters of other c-Jun target genes clearly differed (Fig. 6B, bottom panel) with low DNA methylation at their regulatory regions in GIV gliomas (Chi-square test for two independent groups, FDR<0.05), also observed in other types of human cancer [31]. Methylation of a specific cytosine within a c-Jun motif instance (1 cytosine in the c-Jun motif, “dvTGAGTCAYh”, HOCOMOCO version 11) within the promoters of the potential c-Jun targets was found.…”
Section: Resultsmentioning
confidence: 99%
“…The methylation pattern of the promoters of other c-Jun target genes clearly differed (Fig. 6B, bottom panel) with low DNA methylation at their regulatory regions in GIV gliomas (Chi-square test for two independent groups, FDR<0.05), also observed in other types of human cancer [31].…”
Section: Dna Methylation At the Promoters Of C-jun Putative Targets D...mentioning
confidence: 92%
“…Abnormal DNA methylation is highly associated with the incidence and growth of tumors [31]. Previous studies have shown that RBM10 is related to DNA methylation [32,33].…”
Section: Discussionmentioning
confidence: 99%